Evaluation of Herbicides for Ground Ivy (Glechoma hederacea L.) Control at Two Application Timings. Issue 1 (19th October 2017) - Patton, Aaron J.; Beck, Leslie L.; Weisenberger, Daniel V.; Brosnan, James T.; Breeden, Gregory K.
Abstract : Ground ivy ( Glechoma hederacea L.) is a creeping perennial broadleaf species that is difficult to control in turf. The efficacy of spring herbicide applications has received limited investigation. Further, comparisons between commonly used and effective herbicide treatments are limited. Field experiments were conducted to determine the influence of herbicide selection and fall and spring application timings on the control of ground ivy across three separate environments located across Indiana and Tennessee. Herbicides containing 2, 4‐D, fluroxypyr, triclopyr, iodosulfuron, thiencarbazone, and aminocyclopyrachlor or mixtures of these active ingredients had the greatest control of ground ivy (>53%) at both timings. With the exception of metsulfuron and fluroxypyr, most of the herbicides provided consistent ground ivy control when applied in either the fall or the spring. Differences in ground ivy control between herbicides were much greater than differences between spring and fall application timings. This research indicates that proper herbicide selection has a larger influence on ground ivy control than application timing.